Genomically-selected antifungal Bacillaceae strains improve wheat yield and baking quality - Casal, Alejo; Gizzi, Fernán Oscar; Figueroa, Sol Agostina; Petitti, Tomás Denis; Ferraguti, Facundo Javier; Gaido, Jimena; Torres Manno, Mariano Alberto; Céccoli, Gabriel; Paoletti, Luciana; Dunlap, Christopher; Daurelio, Lucas Damián; Espariz, Martín (Springer, 2025)
Soil microbial diversity degradation through agricultural intensification necessitates sustainable alternatives. This study employed genomic and phenotypic approaches to characterize wheat rhizosphere-associated Bacillaceae for agricultural applications. Initial screening of 576 sporulating isolates for antifungal activity against Fusarium graminearum, followed by RAPD analysis, identified 39 distinct genetic profiles, out of which 15 were classified in Bacillus amyloliquefaciens or Priestia megaterium groups by 16S RNA sequence. Whole-genome sequencing of selected strains enabled precise taxonomic classification and comprehensive trait prediction using in silico tools. Genomic mining revealed strain-specific distributions of beneficial traits, including antimicrobial compound production pathways and plant growth-promoting characteristics. Phenotypic validation confirmed key predicted traits while uncovering additional functionalities not detected in silico. Integration of kernel bioassays, pot experiments, and field trials identified Bacillus velezensis ZAV-W70 and P. megaterium ZAV-W64 as promising biofertilizer and biocontrol candidates, demonstrating enhanced yield without fungicides and improved bread-making quality, respectively. These findings highlight the value of combining genomic analysis with traditional screening methods for developing effective agricultural biologicals, contributing to sustainable wheat production practices.